2017
DOI: 10.1080/16546628.2017.1379862
|View full text |Cite
|
Sign up to set email alerts
|

Antithrombotic mechanism of polysaccharides in Blackberry (Rubus spp.) seeds

Abstract: The blackberry seed was typically removed as a byproduct and waste from blackberry fruits for juices. Developing value-added utilization of berry seeds will significantly expand the market for berry products as well as improve benefit to berry producers. However, the research on blackberry seed is limited. The objective of this paper was to research antithrombotic mechanism of polysaccharides in blackberry seeds. Polysaccharides in blackberry seeds were extracted, purified and identified by high-performance ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Polysaccharides, as an important carbohydrate in nature, are from different sources, such as plant, fungi, and algae, and they exhibit different chemical and biological activities, depending on the structure and nature of the monosaccharides [1]. Due to the physicochemical and functional properties of polysaccharides, i.e., their water retention ability, filming capacity, antioxidant, anti-microbial, immunomodulatory, anti-cancer, constipation, and antithrombus activities [2,3,4,5,6,7], polysaccharides are used in a wide variety of industrial applications, such as food, pharmaceuticals, and textiles. However, inrecent years, due to its high molecular weight, polysaccharides have poor water solubility, so there has been increasing interest in water-soluble polysaccharides as an important class of bioactive substances that may compete with traditional polysaccharides due to their potential biological activities and processing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Polysaccharides, as an important carbohydrate in nature, are from different sources, such as plant, fungi, and algae, and they exhibit different chemical and biological activities, depending on the structure and nature of the monosaccharides [1]. Due to the physicochemical and functional properties of polysaccharides, i.e., their water retention ability, filming capacity, antioxidant, anti-microbial, immunomodulatory, anti-cancer, constipation, and antithrombus activities [2,3,4,5,6,7], polysaccharides are used in a wide variety of industrial applications, such as food, pharmaceuticals, and textiles. However, inrecent years, due to its high molecular weight, polysaccharides have poor water solubility, so there has been increasing interest in water-soluble polysaccharides as an important class of bioactive substances that may compete with traditional polysaccharides due to their potential biological activities and processing properties.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were drawn from the auricular veins of rabbits. After collection, the blood was decalcified by sodium citrate to prevent blood clotting, the serum was separated from the plasma by centrifugation at 3000 rpm at 5 • C for 15 min [41] to assay activated partial thromboplastin time (APTT), prothrombin time (PT), thxrombin time (TT) and fibrinogen (FIB) in vitro.…”
Section: Plasma Anticoagulation Assay In Vitromentioning
confidence: 99%
“…Consumption of blackberries therefore confers numerous health benefits, such as combating oxidative stress and offering anti-inflammatory and anti-cancer effects (Jakobsdottir et al, 2013;Wang et al, 2017). Previous in vitro and in vivo research conducted in our laboratory confirmed that blackberry fruit, especially the seeds of blackberry fruit, contained a wide range of bioactive compounds and exhibited strong antioxidant activity (Yin et al, 2013), liver-protecting properties (Zhang et al, 2014a), α-glucosidase-inhibitory effect (Yong, 2015), blood lipid-reducing function (Yin et al, 2014), antithrombotic capacity (Wang et al, 2017), and diabetes-combating effects (Zhang et al, 2014b). Like other seasonal "soft" fruits with short shelf lives, blackberry is consumed in the form of whole fresh fruit and in processed fruit products (like juice, jam and blackberry wine).…”
Section: Introductionmentioning
confidence: 99%
“…Three polysaccharides isolated from blackberry wine demonstrated anti-inflammatory effects on lipopolysaccharides (LPS) -stimulated RAW264.7 macrophages, significantly reducing the production of nitric oxide (NO) and pro-inflammatory cytokines like tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) (Cordeiro Caillot et al, 2018). In our laboratory, four polysaccharides (called BSP-1a, BSP-1b, BSP-2 and BSP-3) were successfully isolated from blackberry seeds, separated by DEAE-52 column and purified by Sephadex G-100 column (Wang et al, 2017). Three of these four polysaccharides (BSP-1b, BSP-2 and BSP-3) exhibited significant anticoagulant activities and inhibitory effect on thrombus formation in blood stasis studies using a male rabbit model or male/female Sprague-Dawley rat models (Xie et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation